Pengaruh Event Arisan Bola Voli terhadap Kesejahteraan Masyarakat di Kecamatan Banyuputih Kabupaten Batang Tahun 2022 - Praptiwi, Dewiyani Kartika; Annas, Mohamad (Indonesian Journal for Physical Education and Sport, 2023)
Sport is no longer just a physical activity, but sport has been eyed to be used as a sector in the development of the economic industry. For example, in Banyuputih District, the community held a sports event aimed at helping the welfare of the people in Banyuputih District. With the volleyball event, people can sell to help their economy. The purpose of this study is to describe and examine the influence of the welfare of volleyball events in Banyuputih District on people's lives. This research use desciptive qualitative approach. A qualitative approach is expected to be able to describe conditions in the field in a more specific, transparent, and in-depth manner regarding observable speech, writing, or behavior of individuals, groups, communities, or certain organizations. The focus of the research in this study was to describe the impact of holding a volleyball event on the welfare of the people in Banyuputih District, Batang Regency. Researchers used observation data collection techniques, interviews, and documentation. The results of research on 6 villages in Banyuputih District showed that the influence of the volleyball arisan event had a major influence on the economy and social life of the community. Besides that, the volleyball arisan event also influenced the pattern of volleyball coaching in Banyuputih District.